Effects of intra- and inter-day temperature change on acute upper respiratory infections among college students, assessments of three temperature change indicators - Jiang, Feng; Wang, Rensong; Yang, Yongli; Jia, Xiaocan; Ma, Leying; Yuan, Mengyang; Liu, Kangkang; Bao, Junzhe (Frontiers in Public Health, 2024)
Background: Acute upper respiratory infection (AURI) is a significant disease affecting all age groups worldwide. The differences in the impacts of different temperature change indicators, such as diurnal temperature range (DTR), temperature variation (TV), and temperature change between neighboring days (TCN), on AURI morbidity, are not clear. Methods: We collected data on 87,186 AURI patients during 2014-2019 in Zhengzhou. Distributed lag non-linear model was adopted to examine the effects of different temperature change indicators on AURI. We calculated and compared the attributable fractions (AF) of AURI morbidity caused by various indicators. We used stratified analysis to investigate the modification effects of season and gender.Results: With the increase in DTR and TV, the risk of AURI tended to increase; the corresponding AF values (95% eCI) higher than the references (5% position of the DTR or TV distribution) were 24.26% (15.46%, 32.05%), 23.10% (15.59%, 29.20%), and 19.24% (13.90%, 24.63%) for DTR, TV0-1, and TV0-7, respectively. The harmful effects of TCN on AURI mainly occurred when the temperature dropped (TCN<0), and the AF value of TCN below the reference (0 °C) was 3.42% (1.60%, 5.14%). The harm of DTR and TV were statistically significant in spring, autumn and winter, but not in summer, while the harm of TCN mainly occurred in winter. Three indicators have statistically significant effects on both males and females.Conclusions: High DTR and TV may induce AURI morbidity, while the harm of TCN occurs when the temperature drops. The impacts of DTR and TV on AURI are higher than that of TCN, and the impact of few-day TV is higher than that of multi-day TV.The adverse effects of DTR and TV are significant except in summer, while the hazards of TCN mainly occur in winter.